Monitoring oocyte-based human pluripotency acquisition using synchrotron-based FTIR microspectroscopy reveals specific biomolecular trajectories - Dučić, Tanja; Sánchez-Mata, Alicia; Castillo-Sánchez, Jesús; Algarra-González, Manuel; González-Muñoz, María Elena (Elsevier, 2023)
The reprogramming of human somatic cells to induced pluripotent cells (iPSCs) has become a milestone and a paradigm shift in the field of regenerative medicine and human disease modeling including drug testing and genome editing. However, the molecular processes occurring during reprogramming and affecting the pluripotent state acquired remain largely unknown. Of interest, different pluripotent states have been described depending on the reprogramming factors used and the oocyte has emerged as a valuable source of information for candidate factors. The present study investigates the molecular changes occurring in somatic cells during reprogramming with either canonical (OSK) or oocyte-based (AOX15) combinations using synchrotron-radiation Fourier transform infrared (SR FTIR) spectroscopy. The data acquired by SR FTIR indicates different representation and conformation of biological relevant macromolecules (lipids, nucleic acids, carbohydrates and proteins) depending on the reprogramming combination used and at different stages during the reprogramming process. Association analysis based on cells spectra suggest that pluripotency acquisition trajectories converge at late intermediate stages while they diverge at early stages. Our results suggest that OSK and AOX15 reprogramming operates through differential mechanisms affecting nucleic acids reorganization and day 10 comes out as a candidate hinge point to further study the molecular pathways involved in the reprogramming process. This study indicates that SR FTIR approach contribute unpaired information to distinguish pluripotent states and to decipher pluripotency acquisition roadmaps and landmarks that will enable advanced biomedical applications of iPSCs.
Keywords: Medicina regenerativa; Células - Transformación; Células somáticas; Induced pluripotent stem cells (iPSCs); Oocyte; Reprogramming; FTIR; Synchrotron spectroscopy